Contextualization of Mustaḥiq Zakat at LAZNAS Nurul Hayat Surabaya - Muhammad Ufuqul Mubin; Achmad Siddiq (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
This paper discusses the contextualization of mustahiq zakat seen from the changes in its meanings which have expanded to riqâb, ghârim, sabîlillâh and ibn al-sabîl, while other meaning of mustaḥiq is relatively static such as faqîr, miskîn, 'âmil, mu' allaf. Practically, the concept of mustahiq zakat is contextualized by various zakat managers, one of which is Laznas (National Amil Zakat Institute) Nurul Hayat Surabaya. Mustaḥiq zakat which refers to the poor and âmil is contextualized according to the general meaning in classical and contemporary fiqh. While the mustahiq zakat of mu'allaf is contextualized to be limited to people who have converted to Islam, while the concept of mu'allaf in fiqh includes people who have not converted to Islam but have social potential and strength. The mustahiq zakat of riqâb, ghârim, sabîlillâh and ibn as-sabîl are contextualized widely beyond the meaning in fiqh generally. The contextualization of mustahiq zakat by Laznas Nurul Hayat shows that the benefit of humans (maṣâliḥ al-'ibâd) is the main consideration in zakat management, in addition to the contextualization of mustaḥiq zakat is proof that changes in situations, conditions, environment and socio-culture influence the changes in Islamic law. The conclusion in this paper uses the theory of change in Islamic law and uses a normative approach which aim to reveal the truth values ​​in the practice of zakat in society which can be actualized in the future.